The Use of the Wiki and the Improvement in Collaborative Learning - Flores-Cueto, Juan José (2020)
The advancement of technology has allowed the creation of learning environments that favor social interaction, identifying key aspects for the development of collaborative activities, in relation to the formation of groups. The purpose of this study is to determine to what extent the use of the wiki, in the context of teaching through a virtual classroom, allows to improve collaboration in the development of group work of students from a private university in Lima. The quasi-experimental design, with pretest and posttest, an intact group and an experimental group is used as a research method. The instrument used constitutes a rubric that evaluates the dimensions of collaborative learning: positive interdependence, meaning construction and psychosocial relationships. The results showed that the use of the wiki improves collaborative learning in undergraduate students.